1977
DOI: 10.1038/269507a0
|View full text |Cite
|
Sign up to set email alerts
|

High levels of cadmium in Atlantic seabirds and sea-skaters

Abstract: 100% because very limited sample sizes precluded determination of carbon dioxide, moisture, and ignition loss.X-ray diffraction patterns of each sample revealed a poorly-crystalline apatite-like phase representing hydroxyapatite, Caio(OH)2(PO,)G, a major component of calculus"-D. Considerable quartz was also present, together with some calcium silicate, Ca3Si201, or calcium aluminium silicate, CaAhSi,Q". The similarity of the compositions indicates that the teeth were in contact for long periods with ground wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1981
1981
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(14 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…A later paper by Cheng and Harrison (1983) confirmed seabird predation on a related species (Halobates sericeus). None of the birds were of the same species as those in the report by Bull et al (1977), and most of the birds fed only occasionally on the insects. Peden et al (1973) implied that aquatic organisms may be potential sources of Cd for herring gulls (Larus argentatus).…”
Section: D) Aquatic Birds and Mammalsmentioning
confidence: 69%
See 1 more Smart Citation
“…A later paper by Cheng and Harrison (1983) confirmed seabird predation on a related species (Halobates sericeus). None of the birds were of the same species as those in the report by Bull et al (1977), and most of the birds fed only occasionally on the insects. Peden et al (1973) implied that aquatic organisms may be potential sources of Cd for herring gulls (Larus argentatus).…”
Section: D) Aquatic Birds and Mammalsmentioning
confidence: 69%
“…Bull et al (1977) reported Cd levels varying from 1.4 to 57.0 ILgog-t in the livers and 14.6 to 240 ILgog-t in the kidneys of pelagic seabirds and suggested that high levels of Cd in pelagic seabirds reflected possible dietary consumption of contaminated organisms far out at sea. High levels of Cd (up to 25 p.go g-t) reported in seaskaters (Halobates micans) were cited as potential Cd sources for the seabirds.…”
Section: D) Aquatic Birds and Mammalsmentioning
confidence: 96%
“…Schneppenheim ( Bull et al (1977). Anderlini et al (1972), comparing Cd concentrations in petrels and tern eggs from the Antarctic and from North America, found rather similar concentrations at both sites.…”
mentioning
confidence: 62%
“…Sea birds and sea turtles have also been reported as Halobates predators (Senta et al, 1993;Witherington, 2002). Bull et al (1977), Cheng et al (1984) and Schulz-Baldes (1989) have suggested that Halobates micans could be used as a bioindicator of cadmium distribution in the surface waters. Since these insects live at the sea-air interface, they could also be used as indicators of changes in ocean surface layer brought about by anthropogenic action.…”
Section: Discussionmentioning
confidence: 99%